Pengaruh Penerapan Model Pembelajaran Kooperatif Berbasis Portofolio terhadap hasil Belajar PKn Pada Materi Pemerintahan Pusat siswa kelas IV Gugus VI Denpasar Utara - ., Ni Wayan Sri Oktarini; ., Drs. I Ketut Adnyana Putra,M.Pd; ., Drs. Made Putra, M.Pd (Universitas Pendidikan Ganesha, 2014)
The purpose of this study was to determine differences in learning outcomes between students who take the Civics cooperative learning-based portfolio. students who take conventional learning in fourth grade student at North Denpasar cluster VI. This research is an experimental study with a research design that used non-equivalent control group design. Population is involved throughout the fourth grade students in Cluster VI north of Denpasar and samples from this study were all fourth grade students in elementary N 4 Peguyangan kangin as much as the control group and SD 47 N 7 Peguyangan kangin as many as 38 experimental groups. The instrument used to collect data Civics learning outcomes in the control group and the experimental group is an objective test with multiple choice type. Then the data were analyzed using t-test. Based on tests of normality and homogeneity of data from two groups of data obtained both the normal group. Hypothesis testing is done by t-test. The analysis showed, tcount = 3.19, with degrees of freedom (df) 83 and 5% significance level. Retrieved ttabel = 2.000 Accordingly, thitung > ttabel (3.19> 2.000) so that H0 is rejected and Ha accepted. It can be concluded that there are differences in learning outcomes between students who take the Civics cooperative learning-based portfolios with students who take conventional learning in fourth grade student at North Denpasar cluster VI. keyword : Portfolio-based models of cooperative learning, conventional learning models, learning outcomes.